2019
DOI: 10.1101/2019.12.11.872747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combining genotype, phenotype, and environmental data to delineate site-adjusted provenance strategies for ecological restoration

Abstract: Despite the importance of climate-adjusted provenancing to mitigate the effects of climate change, climatic considerations alone are insufficient when restoring highly degraded sites. Here we employ a comprehensive landscape genomic approach to assist the restoration of moderately disturbed and highly degraded sites. Relying on genotyping-by-sequencing we identified thousands of single nucleotide polymorphisms in two plant species of special interest for the restoration of iron-rich Amazon Savannas from the Ea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 87 publications
0
32
0
Order By: Relevance
“…In line with the conceptual premise by Lesica and Allendorf (1999), Carvalho et al. (2020) found that observed and predicted genotypes for the highly degraded restoration site did not cluster together in either species, while the opposite was observed for the moderately disturbed site. In the praxis, this result suggests that local provenances are optimal to restore the moderately disturbed site, whereas mixed seed could be the best strategy to revegetate the highly degraded mining site, as local plants are probably no longer adapted to their climate and soil conditions.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…In line with the conceptual premise by Lesica and Allendorf (1999), Carvalho et al. (2020) found that observed and predicted genotypes for the highly degraded restoration site did not cluster together in either species, while the opposite was observed for the moderately disturbed site. In the praxis, this result suggests that local provenances are optimal to restore the moderately disturbed site, whereas mixed seed could be the best strategy to revegetate the highly degraded mining site, as local plants are probably no longer adapted to their climate and soil conditions.…”
Section: Introductionmentioning
confidence: 65%
“…Plant species suitable for restoration of iron‐ore‐exhausted mining areas in Canga ecosystems in Brazil and examined for neutral and adaptive genetic variation by Carvalho et al. (2020): (a) Dioclea apurensis (photo: Daniela Zappi); (b) Mimosa acutistipula var. ferrea (photo: Pedro Viana); (c) Pristine Canga ecosystem (savannas on the top of mountain plateaus surrounded by evergreen forest) (photo: Leonardo Viana) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations